SEJARAH EVOLUSI TUJUAN KEBIJAKAN KURIKULUM PENDIDIKAN TINGGI INDONESIA SEJAK 1968 - Hesti Wiranota (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The higher education curriculum in Indonesia has undergone several changes with different curriculum policy objective. The changes in the policy objectives of the higher education curriculum since 1968 were divided into three stages; ①Curriculum 1968 (Orde baru);②Curriculum 1994 (Menjelang akhir orde baru);③Curriculum 2000 (Pasca reformasi). This study used historical method to formulate evolution logic results. The results indicated that the policy objectives of the higher education curriculum implemented in 1968 (Orde baru) were guided by strengthening the character of Indonesian students. The higher education curriculum policy at that time was faced with the problem of inadequate indoctrination of the nation's ideological values. The policy objectives of the higher education curriculum implemented in 1994 (Menjelang akhir orde baru) were guided by the mastery of science. It is based on the importance of science and technology. The policy objectives of the higher education curriculum implemented in 2000 (Pasca reformasi) focused on student competencies. It is based on global competition and the demands of college graduate users. In conclusion, ①The higher education curriculum policies must be rooted in the national conditions of the country;②The need for sustainable scientific development;③ The realization of the developing students’ competencies.